Food production based on cowpea (Vigna unguiculata): nutritional importance and health benefits (Research, Society and Development, 2021)
The development and enrichment of food is of great importance not only for industry, but also for improving the nutrition of the population, where new products can be created or existing ones can be optimized. Cowpea is one of the main components of the diet in the Northeast and North regions of Brazil, especially in rural areas, due to its high nutritional value, there is a need to expand the diversification of formulations with this raw material, in order to increase the offer of low-cost products, especially for the low-income population. This work aims to identify the main formulations developed, containing cowpea as raw material, based on a systematic review. Foods containing cowpea flour as well as unprocessed foods have been shown to significantly increase levels of vitamins and minerals, thus making the food more nutritious as a whole. Soon it is concluded that the cowpea carries with it a good versatility in relation to its applicability, making it suitable for incorporation in the most diverse food formulations.